2022
DOI: 10.1038/s41598-022-16012-w
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward leisure, satisfaction with leisure policy, and happiness are mediated by satisfaction with leisure activities

Abstract: This study investigated the effect of attitude toward leisure and satisfaction with leisure policy on satisfaction with leisure activities and level of happiness in Korean caregivers for young children. Data were collected from 864 participants (397 men and 467 women) using the 2018 National Leisure Activity Survey (NLAS). The results showed that there were no significant differences between male and female caregivers in terms of satisfaction with leisure policy, satisfaction with leisure activities, and level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Tian et al (2020) concluded that there was no significant difference between women and men participants in terms of serious leisure and satisfaction among recreational runners. However, there are studies in the literature showing significant differences for gender for serious leisure, satisfaction and perceived health outcome parameters (Doğan, 2021;Elkington and Stebbins, 2014;Raisborough, 2007;Yoo, 2022). These results may be affected by the environment in which the individual lives and the serious leisure activity.…”
Section: Discussionmentioning
confidence: 99%
“…Tian et al (2020) concluded that there was no significant difference between women and men participants in terms of serious leisure and satisfaction among recreational runners. However, there are studies in the literature showing significant differences for gender for serious leisure, satisfaction and perceived health outcome parameters (Doğan, 2021;Elkington and Stebbins, 2014;Raisborough, 2007;Yoo, 2022). These results may be affected by the environment in which the individual lives and the serious leisure activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, they did not find a significant difference between leisure satisfaction and gender variable. Yoo (2022) investigated the effect of attitude towards leisure on the level of satisfaction and happiness in leisure activities in Korean carers. While there was no significant difference between male and female groups, it was found that attitude towards leisure had a strong effect on the level of satisfaction and happiness in leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…Those with a passion for the art of film are more likely to go to the cinema for a movie screening, while classical music enthusiasts will prefer concerts at the philharmonic. Others will regularly choose to spend an evening at the theatre or art gallery (Yoo, 2022). An interesting way to spend leisure time, especially in the long term, is tourism.…”
Section: Ways Of Spending Leisure Timementioning
confidence: 99%